Propositions on Sino-American trade dispute : some helpful ideas from social science - Chan, Steve (Nanyang Technological University, 2020)
This short essay introduces some concepts and propositions from social science research that I personally find helpful in understanding the ongoing Sino-American trade dispute. Naturally, they are not meant to suggest a comprehensive or exhaustive list of factors that inform this topic. Given the purpose and the limits of my essay, I also do not engage any specific theory or method, such as the efficient-market hypothesis or game theory pioneered by well-known Nobel laureates (e.g., Burton Malkiel and Eugene Fama; Thomas Schelling).